High steam-conditioning temperature during the pelleting process impairs growth performance and nutrient utilization in broiler starters fed barley-based diets, regardless of carbohydrase supplementation - Perera WNU; Abdollahi MR; Zaefarian F; Wester TJ; Ravindran V (Elsevier Inc. on behalf of Poultry Science Association Inc., 2021)
The influence of supplemental carbohydrase (Carb) and conditioning temperature (CT) on growth performance, nutrient utilization and intestinal morphometry of broilers (d 1–21) fed barley-based diets was examined in a 2 × 3 factorial arrangement, evaluating 2 levels of Carb (0 and 150 g/tonne of feed) and three CT (60, 74, and 88°C). A total of 288, 1-day-old male broilers (8 birds/cage; 6 cages/treatment) were used. The activities of endo-1,4-β- glucanase, endo-1,3 (4)-β-glucanase and endo-1,4-β-xylanase in the Carb were 800 BGU/g, 700 BGU/g and 2,700 XU/g, respectively. On d 21, ileal digesta was collected for the determination of nutrient digestibility. There was no significant interaction between Carb and CT for any tested parameter. Supplemental Carb, regardless of CT, increased weight gain (WG; P < 0.05) and reduced feed per gain (F/G; P < 0.001) by 30 g/bird and 6.5 points, respectively. Increasing CT to 88°C reduced (P < 0.05) WG, but increased (P < 0.05) F/G compared to the diets conditioned at 60° and 74°C. Regardless of CT, Carb enhanced (P < 0.05) the digestibility of starch and AMEn by 1.15% and 32 kcal/kg, respectively. Compared to the diets conditioned at 60° and 74°C, CT at 88°C reduced (P < 0.05) digestibility of dry matter, nitrogen, phosphorus, gross energy, and AMEn. Birds fed diets conditioned at 88°C showed lower (P < 0.05) starch digestibility compared to those fed diets conditioned at 60°C. Conditioning at 88°C increased (P < 0.05) jejunal digesta viscosity by 10.2% compared to diets conditioned at 60° and 74°C. Overall, Carb supplementation improved WG, F/G, starch digestibility and AMEn in broilers fed barley-based diets, irrespective of CT applied. Conditioning barley-based diets at 88°C impaired the ability of birds to utilize nitrogen, starch, phosphorus and energy, and consequently deteriorated WG and F/G. The lack of significant interactions between Carb and CT indicated that negative impacts caused by high CT on bird performance and nutrient utilization occurred regardless of Carb enzyme supplementation. Supplemental Carb per se could not remedy the adverse effects of high CT.
Keywords: barley; broiler; carbohydrase; conditioning temperature; enzyme; Animal Feed; Animal Nutritional Physiological Phenomena; Animals; Chickens; Diet; Dietary Supplements; Digestion; Glycoside Hydrolases; Hordeum; Male; Nutrients; Steam; Temperature